Methylation level of potato gene OMT30376 regulates tuber anthocyanin transformations - Zhang, Huiling; Zhao, Yanan; Zhao, Xijuan; Zhang, Zhonghua; Liu, Ju; Shi, Minghui; Song, Botao (Frontiers in Plant Science, 2022)
After anthocyanin synthesis, a variety of anthocyanin compounds are produced through further methylation, glycosylation, and acylation to enhance the color phenotype. Such modifications require participation of catalytic enzymes, but the effect of the potato methylase gene on anthocyanin biosynthesis has not been reported. Red and purple mutation types appear in tubers of the potato cultivar ‘Purple Viking’ with chimeric skin phenotypes. In this study, transcriptome and anthocyanin metabolome analyses were performed on skin of Purple Viking tubers and associated mutants. According to the metabolome analysis, the transformation of delphinidin into malvidin-3-O-glucoside and petunidin 3-O-glucoside and that of cyanidin into rosinidin O-hexoside and peonidin-3-O-glucoside were hindered in red tubers. Expression of methyltransferase gene OMT30376 was significantly lower in red tubers than in purple ones, whereas the methylation level of OMT30376 was significantly higher in red tubers. In addition, red skin appeared in tubers from purple tuber plants treated with S-adenosylmethionine (SAM), indicating the difference between purple and red was caused by the methylation degree of the gene OMT30376. Thus, the results of the study suggest that the OMT30376 gene is involved in the transformation of anthocyanins in potato tubers. The results also provide an important reference to reveal the regulatory mechanisms of anthocyanin biosynthesis and transformation.